Coberturas vegetais no desempenho agronômico, qualidade de sementes e componentes bioquímicos em cultivares de soja - Ricci, Thiago Toshio (2012)
Plants produce a large variety of secondary metabolites, which represent an interface between plants and surrounding environment (allelopathy). This way, this study aims to assess the allelopathic effects of the cover plants oat, braquiaria, canola, sorghum and wheat on agronomic performance, seed quality and biochemical components in soybean cultivars. The experiment was conducted at Iguatemi Experimental Farm, which belongs to Maringá State University (UEM), in 2010, crop year 2010/11. The experiment was conducted in a randomized block design, with four replications and the treatments were arranged in split-plots, where plots were made of the cover plants oats, braquiaria, canola, sorghum and wheat plus the control plant (fallow), and the subplots were made of the soybean cultivars NK 7059 RR (RR Vmaxx), BMX Power RR, BRS 316 RR, CD 241 and CD 250 RR RR. After cultivation, the cover plants were dried. Later, soybean cultivars were seeded. In the field, determinations of plant height, height of insertion of the first pod, number of pods per plant, weight of one thousand grains and yield were carried out. In the laboratory, the physiological quality of seeds was evaluated by germination test, accelerated aging, tetrazolium and electrical conductivity test. The sanitary quality was assessed using the method of filter paper or "blotter test". The concentrations of oil and protein in the seeds were determined and the lignin content in the seed coat as well as the total of phenols in the soybean leaves were quantified. There was no significant difference in the results of agronomic performance, seed quality and oil content in seeds when related to any of the cover plants. The results did not allow us to verify allelopathic effect of cover plants on soybean development, not permitting the find, between the used cover plants, of one with allelopathic potential.